2014
DOI: 10.1017/s1463423614000449
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to autism screening in family medicine practice: a qualitative study

Abstract: Participants had differing views on the increased incidence of autism. Most participants attributed the increase to changes in diagnostic criteria. There was no consensus on the benefit of implementing universal screening for autism during the 18- or 24-month visit. Many preferred to identify potential problems through general developmental assessments and observations. No participants used specific screening tools for autism, and only one participant was aware of such a tool (M-CHAT). Lack of adequate trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
88
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 25 publications
3
88
0
2
Order By: Relevance
“…9,21,[85][86][87][88][89][90][91][92] However, in one study, rates of screening in family medicine practices for ASD have been reported to be lower. 94 Feasibility and effectiveness of parent-report screening tools also have been verified. 9,21,86,88 However, despite the success of screening, a few studies have shown that rates of referral to early intervention were good but not universal, and referrals to specialists were low.…”
Section: Incorporating Surveillance and Screening In The Medical Homementioning
confidence: 96%
“…9,21,[85][86][87][88][89][90][91][92] However, in one study, rates of screening in family medicine practices for ASD have been reported to be lower. 94 Feasibility and effectiveness of parent-report screening tools also have been verified. 9,21,86,88 However, despite the success of screening, a few studies have shown that rates of referral to early intervention were good but not universal, and referrals to specialists were low.…”
Section: Incorporating Surveillance and Screening In The Medical Homementioning
confidence: 96%
“…8,9 There are multiple factors that account for the more than the 2-year difference between earliest signs to diagnosis that may delay entry into early intervention (EI) programs. These barriers, which include time-consuming evaluations, 10 cost of care, 11 lack of providers, 12 lack of comfort in diagnosing by primary care providers, 12 and other challenges, each require different approaches in order to begin to close this gap.…”
mentioning
confidence: 99%
“…The high percentage of children in the present study who lost an ASD diagnosis because it was changed (73.5% of 13.1%, or over 9% of all school-aged CSHCN ever diagnosed with ASD) suggests overdiagnosis may be more common in this population than expected. Overdiagnosis could be the result of difficulty distinguishing children with ASD from children who possess language delays or global developmental delays (Lord, 1995) and because variability in the quality of screening and evaluation practices confound diagnostic precision (Fenikile et al, 2014). …”
Section: Discussionmentioning
confidence: 99%